Prosthetic rehabilitation after enucleation of cystic lesion with semi precision attachment and telescopic crown - Deshpande, Varun Aniket; Deshpande, Rucha Varun; Gangji, Praneita S (Indian Journal of Case Reports, 2019)
The demand for a quality dental practice is increasing in today’s era. Along with the form and function of the prosthesis, esthetics is also a matter of concern. Prosthetic rehabilitation of an enucleated cystic lesion becomes challenging in some conditions. Here, we report the case of prosthetic rehabilitation after enucleation of the cystic lesion with semi-precision attachment and telescopic crown in a 30-year-old female. In this case after enucleation of Odontogenic Keratocyst, the prosthesis was fabricated using semi-precision attachment along with the telescopic crown which provided proper retention, stability, and aesthetics.